MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA DENGAN METODE KOOPERATIF STAD - Nursahadah Dasopang (STKIP ROKANIA, 2017)
The purpose of this study was conducted to find out and describe the improvement of student learning outcomes in science subjects withSTADcooperative method.The research method used is the method of researching the action done in two cycles. Each cycle consists of four stages of research, namely planning, implementation, observation, and implementation.This research data is the result of the action of teachers and students in learning, field notes and student learning outcomes. Data on teacher observation and field notes were conducted by cualitative. The results show that STAD cooperative methods that are used as auxiliary tools in learners can increase the effectiveness and productivity of the lesson in the lesson of science lesson to instruct students to solve the weaknesses in learning.Thus, the learning of IPA with STAD cooperative method in grade VI SDN 003 Rambah students showed the average grade increase in cycle 1 that is 50% to 70% on cycle 2.